2009
DOI: 10.1080/13693780903103952
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Blastomyces dermatitidis: implications for PCR detection in clinical and environmental samples

Abstract: Summary Blastomycosis is a serious and potentially fatal infection by the thermally dimorphic fungus Blastomyces dermatitidis. PCR assays targeting the BAD-1 virulence gene promoter have been developed to aid in the detection of the pathogen in clinical and environmental samples. However, little is known regarding the genetic diversity of B. dermatitidis and how this might affect the performance characteristics of these assays. We explored the genetic relatedness of 106 clinical and environmental isolates of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…A large proportion of isolates from this study (104/112; 95%) were examined previously for polymorphisms in the putative promoter region of BAD-1, a surface adhesin and essential virulence factor of B. dermatitidis. In that study, four haplotypes were identified by PCR and sequencing (29). Haplotypes 1 to 3 were very similar to each other except for one or more point mutations and/or small indels.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of isolates from this study (104/112; 95%) were examined previously for polymorphisms in the putative promoter region of BAD-1, a surface adhesin and essential virulence factor of B. dermatitidis. In that study, four haplotypes were identified by PCR and sequencing (29). Haplotypes 1 to 3 were very similar to each other except for one or more point mutations and/or small indels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the BAD1 promoter region has a number of nucleotide polymorphisms, which resulted in the identification of four haplotypes of B. dermatitidis (11,12). In addition to nucleotide polymorphism, a major size disparity due to two large insertions in the BAD1 promoter was also found in many B. dermatitidis strains (12). This can complicate the conventional PCR assay due to either insufficient amplification efficiency or misinterpretation as a nonspecific product.…”
mentioning
confidence: 99%
“…These results were not totally unexpected, as it has been reported previously that there is a significant size and sequence variation in the BAD1 gene amplicon. The differences are the basis of four haplotypes of B. dermatitidis (12). The sequence analysis of the BAD1 gene through a BLAST search revealed that the 24 strains of B. dermatitidis used in the present study belonged to all known H1 to H4 haplotypes (Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations